Evaluate the Role of A. Baumannii in Promoting Inflammation and Meningitis-Related Genes in Various Immune Cells - Mukhlif, Rafal Majid; Noomi, Bashar Sadiq (South Eastern European Journal of Public Health, 2024)
The role of Acinetobacter baumannii in promoting inflammation in spleenocyte and lymph node cells has been studied by detecting the gene expression of four different genes that are related to meningitis, which was performed after treatment of laboratory animal cells with dead cells of A. baumannii, the results of gene expression by using Real Time- Quantitative PCR and graph prism software exhibited the presence of statistical differences between A. baumannii treated and non-treated laboratory animal cells. All genes showed an expression between one and a half (1.5) to more than 40 (>40) fold change. The NLRP has expression in the spleen and lymph nodes between the (2-10) folds, which increase after being activated with killed A. baumannii cells. NF Kappa B has expression in the spleen and lymph nodes between (1.5-6) fold increase after being activated with killed A. baumanniicells. GMCSF has expression in the spleen and lymph nodes between (30-40) fold increase after being activated with killed A. baumannii cells. IL-1B has expression in the spleen and lymph nodes between (4.5-40) fold increase after being activated with killed A. baumannii cells.